Values and facts and fancies - Clark, Stephen R. L. (Religious studies, 2026)
An examination of the apparent gap - familiar in many branches of philosophy - between ‘the facts’ and ‘values’, focusing especially on Sam Gamgee’s perception of ‘Earendil’s Star’ and the real nature of ‘the planet Venus’: Is it possible to trust in the awe and admiration we may feel towards ‘the heavens’ in the light of current astronomical theory about the wider world? How can humane values, including love of beauty, survive in an inhumanly indifferent world? Can obvious fictions have more than allegorical significance? Must we rely on fictions to survive as humane creatures, or may those seeming fictions, and our initial emotional response, provide true guidance to the way things are, and how we might be?